The evolution of China’s English education policy and challenges in higher education: analysis based on LDA and Word2Vec - Hu, Haiyang; Li, Fan; Luo, Zhengying (Frontiers in Education, 2024)
China proposed the Belt and Road Initiative to strengthen regional connectivity so as to embrace a brighter future together. Since the Initiative was put forward, it has brought many challenges to China's English education policies. During the initiative, many scholars have conducted research on China's education policies. However, there is little research that analyzes the evolution of policy themes during the initiative. This study aims to analyze the evolution of the themes and challenges in China's English education policy under the Belt and Road Initiative using the Latent Dirichlet Allocation (LDA) and Word2Vec methods. The study found that after the initiative, the policy focus has changed. For example, English education has shifted from testing abilities to cultivating students' intercultural communication skills in order to meet the cooperation needs with countries alongside the "Belt and Road". Moreover, teaching strategies that were examination-oriented have also changed to emphasize teaching methods and feedback. The focus and teaching strategies have also undergone great changes. At the same time, China's English education policy have shifted from focusing on improving students' writing skills, English proficiency, and creativity to conducting in-depth research and addressing specific issues, including challenges in the areas of investigating and addressing educational challenges, linguistics and media influence, educational institutions and programs, online courses and academic research, attitudes and self-efficacy, use of multiple languages and globalization, teaching and current educational issues, as well as curriculum design and writing. These findings provide in-depth insights into the impact of the Belt and Road Initiative on China's English education policy and offer new directions for future research.